Conversion of biodiesel‐derived glycerol into biotechnological products of industrial significance by yeast and fungal strains. Issue 3 (6th May 2016) - Papanikolaou, Seraphim; Rontou, Maria; Belka, Aikaterini; Athenaki, Maria; Gardeli, Chryssavgi; Mallouchos, Athanasios; Kalantzi, Ourania; Koutinas, Apostolis A.; Kookos, Ioannis K.; Zeng, An‐Ping; Aggelis, George
Abstract : Oleochemical activities (e.g. biodiesel production, fat saponification) generate annually very high amounts of concentrated glycerol‐containing waters (called crude glycerol) as the principal residues of these processes. Crude glycerol is an industrial residue the valorization of which attracts remarkable and constantly increasing interest. In the current investigation, biodiesel‐derived glycerol was employed as substrate for yeast and fungal strains cultivated under nitrogen‐limited conditions in shake flasks. Glucose was employed as reference substrate. Several yeasts ( Candida diddensiae, Candida tropicalis, Pichia ciferrii, Williopsis saturnus, Candida boidinii, and Candida oleophila ) rapidly assimilated glucose and converted it into ethanol, despite aerobic conditions imposed, and were Crabtree‐positive. None of these yeasts produced ethanol during growth on glycerol or accumulated significant quantities of lipid during growth on glucose or glycerol. Only Rhodosporidium toruloides produced notable lipid quantities from glucose and to lesser extent from glycerol. Yarrowia lipolytica LFMB 20 produced citrate ≈58 g/L growing on high‐glucose media, while on high‐glycerol media ≈42 g/L citrate and ≈18 g/L mannitol. During growth on glucose/glycerol blends, glycerol was assimilated first and thereafter glucose was consumed. Fungi produced higher lipid quantities compared with yeasts. High lipid quantities were produced by Mortierella ramanniana, Mucor sp., and mainly Mortierella isabellina, with glycerol being more adequate for M. ramanniana and glucose for Mucor sp. and M. isabellina . M. isabellina ATHUM 2935 produced lipids of 8.5 g/L, 83.3% w/w in dry cell weight (DCW) and conversion yield per unit of glucose consumed ≈0.25 g/g. The respective values on glycerol were 5.4 g/L, 66.6% w/w in DCW and ≈0.22 g/g. Lipids of all microorganisms were analyzed with regards to their fatty acid composition, and M. isabellina presented the closest similitude with rapeseed oil. Crude lipids produced by this fungus and extracted with chloroform/methanol blend, were composed mostly of triacylglycerols, thus indicating that these solvents are adequate for triacylglycerol extraction.